Management of bleeding associated with radiofrequency ablation of benign thyroid nodules - Hu, Kunpeng (J Int Med Res, 2020)
OBJECTIVE: This study was performed to explore the effective management of bleeding associated with radiofrequency ablation (RFA) of benign thyroid nodules. METHODS: Thirty-five patients with benign thyroid nodules who were treated with ultrasound-guided RFA from July 2015 to December 2016 at the Third Affiliated Hospital of Sun Yat-sen University were retrospectively reviewed. The technique efficacy, bleeding, and other complications were assessed during the follow-up period. RESULTS: The mean technique efficacy was 55.6%±22.8% at 1 month and 24.1%±17.1% at 6 months after the procedure. One case of an intranodular haematoma and two cases of voice change (>1 month) were observed. All patients recovered with corresponding treatment. CONCLUSION: Although the incidence of haemorrhage is low, serious haematomas are life-threatening. Therefore, having a comprehensive understanding of the potential complications, an accurate clinical strategy, and adequate technical skills may prevent or help to properly manage these complications.